2011
DOI: 10.33549/physiolres.932075
|View full text |Cite
|
Sign up to set email alerts
|

TRH-Like Peptides

Abstract: TRH-like peptides are characterized by substitution of basic amino acid histidine (related to authentic TRH) with neutral or acidic amino acid, like glutamic acid, phenylalanine, glutamine, tyrosine, leucin, valin, aspartic acid and asparagine. The presence of extrahypothalamic TRH-like peptides was reported in peripheral tissues including gastrointestinal tract, placenta, neural tissues, male reproductive system and certain endocrine tissues. Work deals with the biological function of TRH-like peptides in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…2A and 3A). These post-translational modifications are also characteristics of TRH in vertebrates 80 and therefore it is likely that the same post-translational modifications occur in the TRH-like tetrapeptides in A . japonicus .…”
Section: Resultsmentioning
confidence: 96%
“…2A and 3A). These post-translational modifications are also characteristics of TRH in vertebrates 80 and therefore it is likely that the same post-translational modifications occur in the TRH-like tetrapeptides in A . japonicus .…”
Section: Resultsmentioning
confidence: 96%
“…Several endogenous and synthetic TRH-like peptides with the pGlu-Xaa-Pro-NH 2 ([Xaa 2 ]TRH) sequence have been investigated, where Xaa denotes any natural and unnatural amino acid residues [20][21][22]. For example, [Glu 2 ]TRH (1b; Figure 1) exhibits various CNS actions characteristic to TRH without endocrine effects, which is preferable in the context of CNS drug development [23].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in this study, we investigated the potential CNS effects of [Glu 2 ]TRH-like tripeptides. The replacement of Glu with Asp brought about peptide 1c (Figure 1) [20]. Analogues 1d and 1e with β-Glu and β-homoGlu (β-hGlu) central acidic residue, respectively, were included based on the increased use of β-amino acids because of their unique structural characteristics in the design of the bioactive ligands [26].…”
Section: Introductionmentioning
confidence: 99%
“…During the 1980s, studies in mammals revealed that TRH is produced by hypothalamic paraventricular neurons as well as by other extra-hypothalamic brain areas, whereas TRH-like peptides originate in extraneural tissues, such as the pancreas and gastrointestinal tract [13]. These TRH-like peptides differ from authentic TRH due to the fact that the amino acid histidine of authentic TRH is replaced by neutral or acidic amino acids, such as glutamic acid, glutamine, asparagine, phenylalanine, leucin, valin, tyrosine, and aspartic acid, this accounting for the different degrees of penetrability of these biological potent TRH variants [14].…”
Section: Ofmentioning
confidence: 99%